Acute Pancreatitis In 3 Years Old Girl : A Case Report - Johan Christian Silaen (Sean Institute, 2025)
Acute pancreatitis (AP) is clinically defined as a sudden onset of abdominal pain associated with increased digestive enzymes in the blood and urine. Acute pancreatitis is not necessarily a rare disease, even in children and adolescents and may be life-threatening if it is severe. Therefore, acute pancreatitis should always be considered during the differential diagnosis of prolonged and reccurent abdominal pain in children, and appropriate treatment should be started promptly when necessary. In general, laboratory tests for the diagnosis of AP are not specific, yet amylase and lipase enzyme examination remain helpful to rule out the diagnose. In this report, we present a recurrent abdominal pain 3 years old girl with acute pancreatitis.